1981
DOI: 10.1126/science.7302586
|View full text |Cite
|
Sign up to set email alerts
|

The Hagfish Slime Gland: A Model System for Studying the Biology of Mucus

Abstract: The hagfish slime gland may provide a model system for studying certain aspects of the biology of mucus. Mucus is obtained in nonhydrated form by electrically stimulating the anesthetized hagfish and the secretions are stirred into ammonium sulfate. Centrifugation and filtration are than used to isolate the two major secretory products, mucous vesicles and threads. Specific advantages of the model and potential applications for research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 7 publications
1
51
0
Order By: Relevance
“…A quantity of exudate from a slime gland (a) placed on to a spatula expands to form a column of mucus (b) within 10 seconds (with threads supporting the mucus mass). Drawn from photographs in the paper by Downing et al, (1991). Table of the roles of EPS exuded by multicellular organisms.…”
Section: Production and Function Of Eps In Unicellular Organismsmentioning
confidence: 99%
“…A quantity of exudate from a slime gland (a) placed on to a spatula expands to form a column of mucus (b) within 10 seconds (with threads supporting the mucus mass). Drawn from photographs in the paper by Downing et al, (1991). Table of the roles of EPS exuded by multicellular organisms.…”
Section: Production and Function Of Eps In Unicellular Organismsmentioning
confidence: 99%
“…Stabilized slime was filtered to separate mucin vesicles from thread skeins, and samples of isolated vesicles were quantified and standardized using the linear relationship between vesicle number and absorbance (350 nm) (Downing et al, 1981).…”
Section: Animal Care and Sample Collectionmentioning
confidence: 99%
“…Slime exudate samples were collected from anaesthetized hagfish as described in Herr et al (Herr et al, 2010), and were stored in a stabilization buffer {SB; 0.9 mol l −1 sodium citrate + 0.1 mol l −1 PIPES buffer [piperazine-N,N′-bis(ethanesulfonic acid)], pH 6.7} (Downing et al, 1981;Fudge et al, 2003). Stabilized slime was filtered to separate mucin vesicles from thread skeins, and samples of isolated vesicles were quantified and standardized using the linear relationship between vesicle number and absorbance (350 nm) (Downing et al, 1981).…”
Section: Animal Care and Sample Collectionmentioning
confidence: 99%
“…An agitated hagfish can release an enormous amount of slime from the numerous slime glands lining its body (Ferry, 1941;Strahan, 1959;Downing et al, 1981a;Martini, 1998). In a previous paper (Fudge et al, 2005), we demonstrated that hagfish slime is an extremely dilute assemblage of mucins and seawater held together by a network of fine protein threads.…”
Section: Introductionmentioning
confidence: 99%